(untitled) (Bangladesh Medical Journal, 2024)
The preferred vascular access method for efficient hemodialysis is the arterio-venous fistula (AVF). There is a rising trend in AVF establishment conducted by nephrologists, aiming to alleviate the workload of vascular surgeons and expedite the prompt care of individuals afflicted with end-stage renal disease (ESRD). This descriptive observational study was conducted at the Department of Vascular Surgery, Ibrahim Cardiac Hospital and Research Institute during the period of June 2017 to July 2022. During the data collection period 1700 patients sought care in the Department for arterio-venous fistula creation, among them complete data of 1103 patients were included in this study. Majority of chronic kidney disease (CKD) patients were referred from the Department of Nephrology, BIRDEM for AVF creation in the mentioned timeline. Data were collected pre-designed data collection sheet and data were analyzed using Statistical Package for Social Sciences (SPSS) version- 25. This study shows that most of the patients (80.8%) were in ages 30 - 59 years and more than two-third (67.6%) of them were male; male-female ratio was 2:1. Diabetes mellitus (DM) was detected in nearly half of the patients (47.2%) and more than two-third (67.2%) of them were suffering from hypertension (HTN). Higher failure rate (73.3%) of AVF creation among patients of age group 30-59 years was significant. Failure rate for male patients was 57% and female patients was 43%. The AVF creation failure rates were 100% for patients with hypertension and for diabetes patients was 60.5%. Complications were found in 15.2% of patients. Post-operative edema and hematoma formation were more common (3.2% and 3.5%, respectively) in comparison to other complications. Among the complicated cases, 7 patients (4.2%) required intervention to correct stealing syndrome and AVF salvage was attempted in 43 cases (25.6%); medical management was pursued in 32(19.0%) cases. Majority (51.2%) of cases who were experiencing complications required AVF ligation. This research demonstrates that several significant clinical factors influence the successful establishment of an arterio-venous fistula (AVF) for hemodialysis factors include advanced age, being male, having diabetes (DM) and hypertension (HTN), having a history of Maintenance Hemodialysis (MHD) prior to AVF creation, choosing the wrist or arm as the AVF site, utilizing specific veins (cephalic and basilic) and specific arteries (radial and brachial). Bangladesh Med J. 2023 Sept; 52(3): 1-7